Determination of DNA damage by alkaline halo and comet assay in patients under sevoflurane anesthesia - (:unkn) unknown (SAGE PUBLICATIONS INC, 2009)
In this study, we report data on the possible genotoxic effect of inhalation anesthetic sevoflurane (SVF) by comparing two techniques, comet and alkaline halo assay, in peripheral blood lymphocytes (PBL) of patients before, during, and after anesthesia and in controls. DNA single strand breaks were detected in PBL of malignant breast cancer diagnosed patients (stage II-III), who were undergoing mastectomy. Blood samples were taken before the induction of anesthesia, at 120 min of SVF anesthesia, and on the postoperative fifth day. The nuclear spreading factor (NSF) for each cell was assessed by alkaline halo assay, and the total comet score (TCS) was evaluated by comet assay. A statistically significant increase (P < 0.0001) was observed in the mean NSF at 120 min of anesthesia (38.24 +/- 14.14) as compared with samples before anesthesia (12.33 +/- 6.14), and the mean NSF was significantly decreased after the postoperative fifth day (17.89 +/- 9.44). Similar results were obtained by the comet assay with significant increase (P < 0.0001) in DNA damage at 120 min of anesthesia (79.66 +/- 15.28) as compared with samples before anesthesia (36.30 +/- 11.39). The DNA damage was almost with the preoperative damage rates after the fifth day of anesthesia (43.40 +/- 12.19). In conclusion, the study points out a reversible genotoxic effect of SVF and the similar DNA damage levels obtained by comet and alkaline halo assay indicate that although halo assay has a completely different principle, it can conveniently be utilized for the assessment of DNA single strand breakage in individual mammalian cells with its experimental advantages. Toxicology and Industrial Health 2009; 25: 205-212.
Keywords: alkaline halo assay; comet assay; DNA damage; sevoflurane anesthesia; single strand breaks; OPERATING-ROOM PERSONNEL; SISTER-CHROMATID EXCHANGES; BREAST-CANCER PATIENTS; SINGLE-STRAND BREAKS; HUMAN-LYMPHOCYTES; IN-VITRO; PERIPHERAL LYMPHOCYTES; GENOMIC DNA; CELLS; ISOFLURANE